Social cognitive measures related to exercise behaviour: Validation in Indonesian middle-aged and older adults - Novita Intan Arovah; Kristiann C. Heesch (Elsevier, 2022)
Introduction: Evidence shows that exercise adoption and maintenance are influenced by social-cognitive processes. Instruments have been developed to measure these processes, but none have been validated for use in the Indonesian context. This study aimed to validate scales measuring social cognitive constructs related to exercise in Indonesian middle-aged and older population. Methods: The Self-Efficacy for Exercise, the Exercise Self-Efficacy, the Multidimensional Outcome Expectations for Exercise, the Exercise Goal-Setting, the Exercise Planning and Scheduling, and the Social Support for Exercise Behavior scales underwent forward-backward translation, readability, and content validity assessments with middle-aged and older Indonesian adults (n = 126; age = 61.2 ± 8.2 years, 72% female). Psychometric testing included assessments of internal consistency and 1-week test-retest reliability, convergent validity, known-group validity with self-reported moderate to vigorous physical activity (MVPA), and construct validity using confirmatory factor analyses (CFA). Results: The scales were found to be readable and content valid. Internal consistencies were acceptable to excellent (Cronbach's α = 0.76-0.93). Moderate to good repeatability estimates were demonstrated (ICC = 0.72-0.88). Convergent validity was supported by moderate correlations between scale scores and MVPA (r = 0.42-0.72). Participants with sufficient MVPA levels consistently scored higher on scales than those with insufficient PA levels. The CFA showed a moderate fit for all scales except the Social Support for Exercise Behavior scale. Conclusion: Although the factor structure of the Social Support scale warrants further investigation, the evidence supports the use of the six scales in Indonesian middle and older adults, including for evaluating the impact of theory-based physical activity interventions in this population.